Pengaruh Harga Tiket, Fasilitas dan Lokasi terhadap Kepuasan Pengunjung pada Kolam Renang Tirta Bening - Narlita Sari; Rike Kusuma Wardhani; Suseno Hendratmoko (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study was conducted to examine the influence of ticket prices, facilities, and location on visitor satisfaction at Tirta Bening Swimming Pool. The approach used was quantitative with data collection through primary and secondary sources. The study population consisted of all visitors to Tirta Bening Swimming Pool. Data analysis techniques used included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that partially, the three variables—ticket prices, facilities, and location—influence visitor satisfaction, as indicated by the t-test results. Meanwhile, based on the F-test, all three simultaneously also have a significant influence on the level of visitor satisfaction. More specifically, the facility variable has a dominant influence on visitor satisfaction. This indicates that comfort, cleanliness, completeness of facilities, and the quality of service provided by the management significantly influence visitors' perceptions of their experience at the swimming pool. Affordable ticket prices are also a major attraction, especially for families and student groups seeking cost-effective recreational alternatives. Meanwhile, the strategic and easily accessible location is also an added value, especially for visitors from the surrounding area. The implications of these findings are the importance of regularly upgrading and maintaining facilities, as well as providing additional services such as a cafeteria, comfortable changing rooms, and responsive security personnel. Management is also advised to periodically evaluate ticket pricing to maintain competitiveness while still supporting operational and service development. Furthermore, location promotion through social media and digital platforms can also expand visitor reach. This research provides an important contribution to the development of tourism destination marketing and management strategies based on visitor needs and satisfaction.